PENGUATAN PENDIDIKAN KARAKTER KEAGAAMAN BERBASIS TRADISI LOKAL MADURA NYABIS - Maulidi, Achmad; wardi, Moh.; Tohir, Ali; Luqman, Kamila (Reflektika, 2021)
In the local Madura tradition there is an Islamic tradition which has been carried out by the local community for a long time and continues to be preserved, in this tradition there is the figure (kiyai) become a center because of his social status who is the highest figure in religion and is very influential on society and its changes in religious matters. The purpose of this research is to find out the process of strengthening the religious character of the community through this tradition. This research approach uses a qualitative type of phenomenological study, data is collected by interview observation and documentation methods while data processing is done by reduction, presentation and verification of data. The results of this study are; The strengthening of religious character in this tradition occurs as in Thomas Likona's theory which starts from a process of moral knowledge that has been agreed upon naturally by society which is then translated into attitudes and behavior or as values and norms in life.